Systematic review and meta-analyses of randomized controlled trials examining tinnitus management - Hoare, Derek J (Wiley Subscription Services, Inc., A Wiley Company, 2011)
OBJECTIVES/HYPOTHESIS: To evaluate the existing level of evidence for tinnitus management strategies identified in the UK Department of Health's Good Practice Guideline. STUDY DESIGN: Systematic review of peer-reviewed literature and meta-analyses. METHODS: Searches were conducted in PubMed, Cambridge Scientific Abstracts, Web of Science, and EMBASE (earliest to August 2010), supplemented by hand searches in October 2010. Only randomized controlled trials that used validated questionnaire measures of symptoms (i.e., measures of tinnitus distress, anxiety, depression) were included. RESULTS: Twenty-eight randomized controlled trials met our inclusion criteria, most of which provide moderate levels of evidence for the effects they reported. Levels of evidence were generally limited by the lack of blinding, lack of power calculations, and incomplete data reporting in these studies. Only studies examining cognitive behavioral therapy were numerous and similar enough to perform meta-analysis, from which the efficacy of cognitive behavioral therapy (moderate effect size) appears to be reasonably established. Antidepressants were the only drug class to show any evidence of potential benefit. CONCLUSIONS: The efficacy of most interventions for tinnitus benefit remains to be demonstrated conclusively. In particular, high-level assessment of the benefit derived from those interventions most commonly used in practice, namely hearing aids, maskers, and tinnitus retraining therapy needs to be performed.